2017
DOI: 10.3892/ijo.2017.4159
|View full text |Cite
|
Sign up to set email alerts
|

BC-02 eradicates liver cancer stem cells by upregulating the ROS-dependent DNA damage

Abstract: Cancer stem cells (CSCs) are responsible for chemoresistance, tumor recurrence and metastasis. Reportedly, aminopeptidase N (APN, also known as CD13) is a marker for semi-quiescent CSCs and a therapeutic target in human liver CSCs. In the present study, the effect of BC-02, a compound obtained by conjugating a CD13 inhibitor bestatin and fluorouracil (5-FU), was investigated toward liver CSCs. Tumor spheres formed in serum-free culture conditions have been successfully used to enrich CSCs. In this study, the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 33 publications
(45 reference statements)
0
18
0
Order By: Relevance
“…Specifically, it has been shown that TICs generally maintain low levels of ROS, due in part, to increased activity of antioxidant enzymes or ROS scavenging molecules 28 . In addition, ROS levels were found to be higher in ovarian and liver non-TIC cultures in comparison to TIC cultures 29,30 . We assume that CuO-NPs specifically inhibit the ability of TICs to maintain low ROS levels.…”
Section: Discussionmentioning
confidence: 90%
“…Specifically, it has been shown that TICs generally maintain low levels of ROS, due in part, to increased activity of antioxidant enzymes or ROS scavenging molecules 28 . In addition, ROS levels were found to be higher in ovarian and liver non-TIC cultures in comparison to TIC cultures 29,30 . We assume that CuO-NPs specifically inhibit the ability of TICs to maintain low ROS levels.…”
Section: Discussionmentioning
confidence: 90%
“…The same authors linked TGF-β-induced EMT to CD13 upregulation, promoting CSC survival by abrogating ROS production [183]. Several experimental approaches have been designed to target CD13 in HCC, most of them showing promising efficacy, especially in combination with cytotoxic agents [184][185][186][187][188][189]. The above-mentioned ubenimex is a protease inhibitor blocking CD13 activity and has been evaluated in other diseases; i.e., squamous cell lung carcinoma, lymphedema and pulmonary hypertension.…”
Section: Mechanisms Of Resistance To Therapy Of Cscsmentioning
confidence: 99%
“…Compound BC-02 can be degraded into bestatin and 5FU ( Dou et al, 2017 ). And BC-02 could inhibit the viability of PLC/PRF/5 and Huh7 cells more effectively, compared with single treatment of bestatin, 5FU, or a combination of 5FU and bestatin ( Figures 4A,B ).…”
Section: Resultsmentioning
confidence: 99%
“…Excess of ROS induces cytotoxicity and apoptosis of cancer cells. Our previous work also indicated that BC-02 impaires the properties of liver CSCs by targeting CD13 and upregulating the intracellular ROS and ROS-induced DNA damage ( Dou et al, 2017 ). APN inhibitor 4cc also synergizes the antitumor effects of 5FU in human liver cancer cells via ROS-mediated drug resistance inhibition and concurrent activation of the mitochondrial pathways of apoptosis ( Sun et al, 2015 ).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation